Hysterectomy : exploring your options - Wallach, Edward E., 1933- (Johns Hopkins Press health book., 2003)
Annotation Hysterectomy is the second most common major surgical procedure performed on women in the United States. Because of new nonsurgical treatments and the rising opposition to the procedure from women's and patients' groups, hysterectomies are performed less frequently than in the past, but many disorders of the uterus - fibroid tumors, uterine and cervical cancer, pelvic inflammatory disease, endometriosis, adenomyosis, and uterine prolapse - still may require surgical treatment. For some women, the decision to have a hysterectomy is an easy one; for others, it is a difficult choice associated with concerns about risks, discomfort, and female identity. In Hysterectomy: Exploring Your Options, experienced gynecologists Edward Wallach and Esther Eisenberg provide complete and up-to-date information about every aspect of the procedure. Written with compassion for all women, this indispensable guide explains the anatomy of the uterus, describes the symptoms of gynecological disorders that may require hysterectomy, discusses the full range of diagnostic tests and treatments, provides details of the surgery itself and postoperative recovery, includes details about other approaches to treatment, and examines long-term consequences involving sexual and reproductive issues as well as hormone replacement therapy. Also included is useful advice about how to talk with your doctor and case studies illustrating the real-life experiences of a variety of women. In Hysterectomy: Exploring Your Options, women will find the information they need to work with their physicians to make informed decisions about their health care.